Socio-cultural factors and capacity building in Interaction Design: Results of a video diary study in Botswana. Issue 135 (March 2020) - Sharp, Helen; Lotz, Nicole; Mbayi-Kwelagobe, Letsema; Woodroffe, Mark; Rajah, Dino; Turugare, Ranganai
Highlights: The study participants were Motswana novice designers, taught by local educators. Not all socio-cultural factors (SCFs) considered during design are in prototypes. Included SCFs are found in many cultures and contexts, e.g. those related with age. Five basic interaction design techniques were used by participants. The findings have implications for building capacity in interaction design. Abstract: This paper presents the results of a video diary study that was conducted with ten novice interaction designers in Botswana, to investigate socio-cultural factors (SCFs) in interaction design. The overall aim of this research is to gain new insights into design behaviour in different cultures in order to inform international interaction design capacity building. To this end, this research investigates what SCFs are considered during the design process, which are accounted for in prototype designs and which interaction design concepts participants use to implement SCFs in their designs. The results reveal 13 categories of SCFs considered during the design process, 10 of which were implemented in prototypes. Participants used five main interaction design concepts to implement SCFs: simplicity, wearable devices, accessibility, universal design, and conversational interaction. In addition, they tended to rely on adaptations to existing products rather than creating new designs. Recommendations for capacity building include the need to identify concrete examples and alternative interaction design concepts that focus on a wider set of SCFs; and to draw upon the synergy between local product design practices and interaction design practices in order to learn how to transition SCFs into interactive products.